2011
DOI: 10.1007/s00542-011-1409-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and evaluation of a thermal microfluidic sensor fabricated on plastic substrate

Abstract: The simulation and the experimental evaluation of a thermal microfluidic flow sensor are presented in this work. The sensor was evaluated in calorimetric mode with water flow. The simulation was performed with COMSOL package. Various combinations of microchannel geometries were tested in different input flows. The optimum pair of upstream-downstream sensing elements were extracted theoretically and verified experimentally. The operational parameters of the device were simulated by 3D models and the optimum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They found that the velocity detection limit is about 5 mm/s, which is in the range of the critical velocity for the transition to the mixed convective flow. Microchannels realized by microfluidic structures were used for measuring very low flow rates as reported by some authors, such as, Buchner et al [8] and Patsis et al [9]. In these two reports water flow was used for the evaluation of the thermal flow sensors.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the velocity detection limit is about 5 mm/s, which is in the range of the critical velocity for the transition to the mixed convective flow. Microchannels realized by microfluidic structures were used for measuring very low flow rates as reported by some authors, such as, Buchner et al [8] and Patsis et al [9]. In these two reports water flow was used for the evaluation of the thermal flow sensors.…”
Section: Introductionmentioning
confidence: 99%